The Best Bug to be - Johnson, Dolores (Macmillan Publishers Company, 1992)
At first disappointed at getting the role of a bumblebee instead of one of the leads in the school play, Kelly makes her part the best one of all.
Keywords: Schools - Fiction; Theater - Fiction